(untitled) (Annals of Medical Research, 2023)
Aim: The foods that we eat don’t just impact our physical health. The link between what we eat and how we feel has become a trending topic. However, knowledge on the effects of diet types on this relation is still limited. The first aim of this study is to reveal the possible link between diet types and eating behaviors, anxiety and depression. Second one is to predict possible variables (demographic, health-related and medical) which cause higher depression scores among individuals following a meat-free diet and an omnivore diet. Materials and Methods: A questionnaire-based survey cross-sectional study was conducted among individuals with a meat-free diet and an omnivore diet (N = 836 with a vegan or a vegetarian diet, N = 519 with an omnivore diet) using an online questionnaire. Demographic, health-related and medical characteristics, The Three-Factor Eating Questionnaire-R 21, Hospital Anxiety and Depression Scale were used to assess variables. Results: A meat-free diet group showed significantly lower anxiety and depression scores, lower cognitive restraint, lower emotional eating and lower uncontrolled eating than omnivore diet group. Shared predictors of depression were dissatisfaction with physical appearance, uncontrolled eating and smoking in both meat-free diet group and omnivore diet group. Lower cognitive restraint and lower education level were predictors of depression in only omnivore diet group. Conclusion: This study revealed that an omnivore diet may be more associated with anxiety, depression, and some disordered eating behaviors than a meat-free diet.